The Study of Laccase Activity as a Biosensor for Peatland Degradation in Oil Palm Plantations in Pesisir Selatan of West Sumatra: The Study of Laccase Activity as a Biosensor for Peatland Degradation in Oil Palm Plantations in Pesisir Selatan of West Sumatra - Harianti, Mimien; Budi Prasetyo, Teguh; Maira, Lusi; Junaidi, Junaidi; Herviyanti, Herviyanti; Anwar, Syaiful; Kasim, Susilawati (Andalasian International Journal of Applied Science, Engineering and Technology, 2023)
The aim of the research was to study enzyme activity as biosensors for peatland degradation in oil palm plantations. The study was conducted in Pesisir Selatan,West Sumatra, on two peatlands with different thicknesses and location coordinates, namely peat with a thickness of <3 m S: 02o18'45.5", 101o00’37.3” and peat with a thickness >3 m S: 02o20’07.5”, E: 101o00’22”. The oil palm in these two locations is 11 years old (planting year of 2007). Observations and sampling of peatlands were carried out on the plantation blocks using the transect method. The transect was set perpendicular to the drainage canal. Peat samples were collected outside the roots (non-rhizosphere) of oil palm. Observation sites were at a distance of 5, 15, 25, 50, 75, 100, 150 m from the edge of the drainage canal and at the thickness of the root layer of 0-25 and 25-50 cm. Peat characteristics observed were water table level, laccase activity, water content, pH, total Fe, and Cu. The water table level in one transect ranged from 60-80 cm and was still within tolerable limits. The laccase activity as a peat degradation biosensor in oil palm plantations in Pesisir Selatan peatland was higher in the 0-25cm layer with an average of <0.5 µmol/g. The increase in water content decreased the laccase activity along with increasing of the distance from the drainage canal and the thickness of the peat layer. The increase in Fe and Cu resulted from increased levels of ash, particularly in peat with a thickness of <3 m, may suppress laccase activity. Peatland in the oil palm plantation of Pesisir Selatan is still relatively stable despite the decomposition processes characterized by laccase activity as a biosensor for peat degradation.